(untitled) (International Journal of Engineering and Computer Science, 2016)
A lossless data hiding scheme in the predicted frames during the motion estimation is proposed in this paper. The main objective of this work is to provide an efficient, low complex and faster data hiding scheme for the video sequences in compressed domain. This work utilized the concept of motion estimation from which the predicted frames are used to hide the data. This method also provides high embedding capacity while preserving the quality of the frames. Experimental results shows that the proposed approach is providing good results in terms of extracted message bits and the quality of the embedded frames.